Predictive value of combined serum IL-6 with UREA on severity of neonatal pneumonia: an observational study - Li Ci; Xu Zhe; Sun Hongqi; Yang Liu; Nie Manjie; Gong Weihua; Yang Junmei; Li Tiewei (Journal of Laboratory Medicine, 2023)
IL-6 is an inflammatory marker and urea nitrogen (UREA) is a common indicator of glomerular filtration function. Their combined detection has predictive value for the severity of neonatal pneumonia.